Mechanisms of Thrombocytopenia During Septic Shock: A Multiplex Cluster Analysis of Endogenous Sepsis Mediators. Issue 6 (June 2018) - Bedet, Alexandre; Razazi, Keyvan; Boissier, Florence; Surenaud, Mathieu; Hue, Sophie; Giraudier, Stéphane; Brun-Buisson, Christian; Mekontso Dessap, Armand
ABSTRACT: Background: Thrombocytopenia is a common feature of sepsis and may involve various mechanisms often related to the inflammatory response. This study aimed at evaluating factors associated with thrombocytopenia during human septic shock. In particular, we used a multiplex analysis to assess the role of endogenous sepsis mediators. Methods: Prospective, observational study. Thrombocytopenia was defined as an absolute platelet count <100 G/L or a 50% relative decrease in platelet count during the first week of septic shock. Plasma concentrations of 27 endogenous mediators involved in sepsis and platelet pathophysiology were assessed at day-1 using a multi-analyte Milliplex human cytokine kit. Patients with underlying diseases at risk of thrombocytopenia (hematological malignancies, chemotherapy, cirrhosis, and chronic heart failure) were excluded. Results: Thrombocytopenia occurred in 33 (55%) of 60 patients assessed. Patients with thrombocytopenia were more prone to present with extrapulmonary infections and bacteremia. Disseminated intravascular coagulation was frequent (81%) in these patients. Unbiased hierarchical clustering identified five different clusters of sepsis mediators, including one with markers of platelet activation (e.g., thrombospondin-1) positively associated with platelet count, one with markers of inflammation (e.g., tumor necrosis factor alpha and heat shock protein 70), and endothelial dysfunction (e.g., intercellular adhesion molecule-1 and vascular cell adhesion molecule-1) negatively associated with platelet count, and another involving growth factors of thrombopoiesis (e.g., thrombopoietin), also negatively associated with platelet count. Surrogates of hemodilution (e.g., hypoprotidemia and higher fluid balance) were also associated with thrombocytopenia. Conclusion: Multiple mechanisms seemed involved in thrombocytopenia during septic shock, including endothelial dysfunction/coagulopathy, hemodilution, and altered thrombopoiesis. Abstract : Supplemental Digital Content is available in the text